Stima in via equitativa dei danni alle aree forestali percorse dal fuoco - Francesco Carbone (Aestimum, 2009)
National law 353/2000 classified forest fire damages as environmental damages, moreover, it indicates the specific components that have to be included in the evaluation process of the damage. Financial components are the first part of this total damage, according to the difficulties of evaluating environmental impacts and specific components indicated by 353/2000 law. The author investigates the numerous addendums that are part of forest fire damage.